Advances and novel developments in environmental influences on the development of atopic diseases - Alkotob, Shifaa Suhayl; Cannedy, Cade; Harter, Katharina; Movassagh, Hesam; Paudel, Bibek; Prunicki, Mary; Sampath, Vanitha; Schikowski, Tamara; Smith, Eric; Zhao, Qi; Traidl‐Hoffmann, Claudia; Nadeau, Kari C. (Allergy (Copenhagen), 2020)
Although genetic factors play a role in the etiology of atopic disease, the rapid increases in the prevalence of these diseases over the last few decades suggest that environmental, rather than genetic factors are the driving force behind the increasing prevalence. In modern societies, there is increased time spent indoors, use of antibiotics, and consumption of processed foods and decreased contact with farm animals and pets, which limit exposure to environmental allergens, infectious parasitic worms, and microbes. The lack of exposure to these factors is thought to prevent proper education and training of the immune system. Increased industrialization and urbanization have brought about increases in organic and inorganic pollutants. In addition, Caesarian birth, birth order, increased use of soaps and detergents, tobacco smoke exposure and psychosomatic factors are other factors that have been associated with increased rate of allergic diseases. Here, we review current knowledge on the environmental factors that have been shown to affect the development of allergic diseases and the recent developments in the field.